What makes the tennis ball go: push through, pull through, and the 400 Watt tennis player - Kibler, W. B. (2001)
Tennis requires sequenced activation of muscles and movement of bones and joints to achieve the motions, positions, and velocities seen in the player. This sequencing is known as the kinetic chain. Proper sequencing results in efficient force and motion production. Richard Schonbörn has calculated that the professional tennis player requires about 400 Watts of power to execute the serve. This is probably the high end of the power development requirement- other players at other levels probably need less, but should strive towards this level of power. We have calculated that more than half of the kinetic energy and power should be developed from the leg and trunk. This would allow the power to be transferred efficiently to the hand to move the hand and racquet maximally into the ball. Based on EMG and video studies, tennis players appear to use two different strategies to move the hand into the ball. The predominant way is the "push through", in which the knees flex and the hip counter-rotates in cocking, the player pushes against the ground, rotates the hip into the serve, and drives the arm up and through the ball by shoulder internal rotation and arm pronation. This allows maximal use of the kinetic chain to develop the power close to the 400 Watt goal. The muscle activations are high in the dominant hamstring and gluteus medius, and in the non-dominant gluteus medius. The second method is the "push through", in which the player fails to adequately flex the hip and/or counter-rotate the hip in cocking. This does not allow hip rotation into the serve. The arm is moved forward by active trunk flexion or abduction, and results in the back hip being pushed backwards as the trunk flexes, rather than the back hip going up and forward as the trunk rotates. The highest muscle activations are seen in the non-dominant external obliques. This method is less efficient in power and force generation, decreases the player`s ability to hit "up and through" the ball in the serve, and requires more muscle activation to approach the 400 Watt level. This is especially noted in the second serve, requiring the player to hit a slice rather than a topspin serve. In general, males tend to hit with the "push through" pattern, and the females tend to hit with the "pull through" pattern. The reasons for these patterns are unclear. It may reflect grip on the tennis racquet or personal preference, but it also may relate to the known gender differences in muscle activation in the hip and proximal leg muscles. Males use the glutei and hamstrings for power development and core stability to a greater extent than females, although the differences are trainable and modifiable by specific strength training using closed chain plyometric exercises. Similarly, methods of tennis technique teaching have been developed to teach proper body movements to establish the "push through" pattern. If players are striving to develop maximum power in the tennis strokes, they should use the kinetic chain to help them towards the 400 watt goal. The "push through" biomechanical pattern would seem to be the most efficient method to achieve maximum results.